Managerial accounting for business decisions - Proctor, Ray (Prentice Hall/Financial Times, 2006)
"Managerial Accounting for Business Decisions helps students who are new to the subject to understand how the techniques of management accounting are used to solve business problems." "Focusing squarely on the needs of today's business, management and non-specialist accounting students, the aim of this book is to set management accounting into a contemporary real world context, helping students to apply the theories they learn to management situations and to use clear thinking to obtain the best financial outcome." "An ideal text for 'Introduction to Management Accounting' courses for business, management and non-specialist accounting students at MBA or undergraduate level. Teaching resources are available online at: www.pearsoned.co.uk/proctor."--BOOK JACKET.